2017
DOI: 10.1002/adsc.201700086
|View full text |Cite
|
Sign up to set email alerts
|

Bis(cycloocta‐1,5‐diene)nickel‐Catalyzed Carbon Dioxide Fixation for the Stereoselective Synthesis of 3‐Alkylidene‐2‐indolinones

Abstract: Ab is(cycloocta-1,5-diene)nickel-catalyzed highly regio-and (E)-stereoselectivehydrocarboxylation of 2-alkynylanilines under very mild conditions has been developed to afford( E)-[2-(o-aminophenyl)]acrylic acids,w hich coulde asily be converted to (E)-3-alkylidene-2-indolinones with important potential bioactivity. Thes tereoselective syntheses of two biologically active molecules,( E)-3-benzylidene-2-indolinone( chemo-preventive potential in inducing NQO1 activity) and (E)-3-(3-methylbutylidene)-2-indolinone(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…8 In the last few decades, numerous protocols have been developed for the synthesis of novel indolin-2-ones. For instance, palladium (Pd)-catalysed intramolecular hydroarylation of N-arylpropiolamides, 9 Knoevenagel condensation of oxindole and aldehyde, 10 two-step protocols such as Ni-catalyzed CO 2 insertion followed by coupling reaction, 11 Pd-catalysed C-H functionalization/intramolecular alkenylation, 12 Pd(0)/ monophosphine-promoted ring-forming reaction of 2-(alkynyl)aryl isocyanates with organoboron compound, and others. 13 Knoevenagel condensation is one of the best methods for the preparation of 3-benzylidene-indolin-2-ones, but oen it gives mixture of E/Z isomeric products.…”
mentioning
confidence: 99%
“…8 In the last few decades, numerous protocols have been developed for the synthesis of novel indolin-2-ones. For instance, palladium (Pd)-catalysed intramolecular hydroarylation of N-arylpropiolamides, 9 Knoevenagel condensation of oxindole and aldehyde, 10 two-step protocols such as Ni-catalyzed CO 2 insertion followed by coupling reaction, 11 Pd-catalysed C-H functionalization/intramolecular alkenylation, 12 Pd(0)/ monophosphine-promoted ring-forming reaction of 2-(alkynyl)aryl isocyanates with organoboron compound, and others. 13 Knoevenagel condensation is one of the best methods for the preparation of 3-benzylidene-indolin-2-ones, but oen it gives mixture of E/Z isomeric products.…”
mentioning
confidence: 99%
“…Soulieotine is an alkaloid which was isolated from the rhizomes of Souliea vaginata, a Chinese folk medicine exhibiting anti-inflammatory and analgesic activities. Previously reported methods for the total synthesis of this compound relied mainly on the palladium catalyst or organic zinc reagent. , In contrast, based on our protocol, the soulieotine could be readily obtained starting from the commercially available 3-bromophenol and 3-methylbut-2-enal (Scheme , route 1). It is worth mentioning that the great functional compatibility of this reaction would pave the way for further expanding the scope of soulieotine derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…However, this method usually led to a mixture of geometrical isomers with unsatisfactory E / Z ratios, and the synthesis of oxindoles, especially for the hydroxy group containing oxindoles, is tedious . Other effective synthetic methods include Co/Rh or Pd/Cu bimetallic catalyzed CO insertion and Ni/Zn-promoted regio- and E -selective CO 2 addition (Scheme B), Pd-catalyzed cross-dehydrogenation coupling of 2,3-diarylacrylamides or N -cinnamoylanilines (Scheme C) as well as a Suzuki-type reaction based on 2-iodo-arylpropynamides or 2-(alkynyl)­aryl isocyanates (Scheme D). Although these methods were practical and applicable for the construction of 3-arylideneindolin-2-ones, most of them still suffered from limitations such as unfavorable geometrical selectivity, poor availability of starting materials, necessity for noble metal catalysts, and the requirement of over stoichiometric amounts of oxidants. In addition, as far as we are aware, very few methods have been established for the synthesis of hydroxylated 3-arylideneindolin-2-ones, which would, therefore, provide useful handles for further transformations .…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Ma and other research groups reported the formation of 3‐alkylideneindolin‐2‐ones through the cyclization of 2‐alkynylanilines in the presence of carbon dioxide/carbon monoxide using palladium, rhodium and nickel catalysts (Equation 4 in Scheme 1). [ 7 ] Zhu et al [ 8 ] and Li et al [ 9 ] independently developed palladium‐catalyzed domino carbopalladation/C–H activation/C–C bond‐forming reactions that employs an anilide sp 2 C–H bond and either an electrophilic reagent (Ar‐I) or a nucleophilic reagent (Ar‐H, R‐OH, R‐CO 2 H, ArI(OAc) 2 , and phthalimide) as the coupling partners to give 3‐alkylideneindolin‐2‐ones (Equation 5 in Scheme 1). Nagasawa's group demonstrated the formation of 3‐alkylideneindolin‐2‐ones from N ‐cinnamoylanilines via palladium‐catalyzed aromatic C–H activation and intramolecular alkenylation (Equation 6 in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%